Anatomia dos frutos do cultivar de tomateiro "Alcobaça" em diferentes períodos de armazenamento - Rocha Leal , Nilton; Shimoya, Chotaro (Revista Ceres, 2025)
Cytological observations were made on tomato fruits of 'Alcobaça' cultivar, that were stored under natural conditions for 1, 7, 8, and 9 months after harvest. The pericarp was studied in detail. Fresh tissue from the equatorial region of the fruit was examined. Many changes occurred in the pericarp region of the fruit as time of storage increased. Thus, the fruits of 'Alcobaça’ have a longer storage life because the pericarp changes.